KAJIAN POTENSI PERIKANAN TANGKAP DAN PERTUMBUHAN JUMLAH KAPAL TANGKAP ( PURSE SEINE) DI KABUPATEN PEKALONGAN - Sri Waluyo, Bambang (Department of Naval Architecture - Diponegoro University, 2009)
In this paper Growing up Catching Vessel every year in District Pekalongan become CPEU Drop in every year. One of Thegreat potential of Indonesian ocean is fishing catch. Cause Indonesia have 17.502 island and have longest margine line island after Canada about 81.000 km, with convention PBB ( UNCLOS ) 1982 Indonesia have 3,1 million km2 and additional 2,7 million km2cause we have ZEEI. The condition make Indonesia have very big Ocean potention fish catching about 6,4 Million ton/year